To analyze whether Oliver's work is accurate, let's carefully review the steps given in the table and the correct application of the Zero Product Property.
Starting from the equation:
\[ (x + 3)(x + 4) = 0 \]
According to the Zero Product Property, for the product of two factors to equal zero, at least one of the factors must be equal to zero:
- Set \(x + 3 = 0\)
- Set \(x + 4 = 0\)
Solving these equations:
- \(x + 3 = 0 \Rightarrow x = -3\)
- \(x + 4 = 0 \Rightarrow x = -4\)
Oliver’s table suggests:
- \(x - 3 = 0\) -> \(x = 3\) (incorrect)
- \(x + 4 = 0\) -> \(x = -4\) (correct)
From the table, there is a mistake in the first row where it states \(x - 3 = 0\) instead of \(x + 3 = 0\).
Therefore, the correct root from the first factor should be \(x = -3\), not \(x = 3\).
So based on the analysis, the accurate response to the question is:
No, \(x - 3 = 0\) in the second row should be \(x + 3 = 0\).